Object Lessons: Teachers, Historians, Narratives and Inquiry. Issue 1 (1st January 2006) - Gerwin, David
This paper focuses on the museum education aspects of a programme designed to improve the teaching of American history in some New York City public schools. The U.S. Department of Education's Teaching American History Grant programme awarded nearly 1 million to a 3-year collaboration between the New-York Historical Society, the Alternative Schools, and Queens College. During three Summers Institutes held each year, historians, history educators, and teachers worked with materials in the New-York Historical Society. One historian interrogated Washington's field cot to get at issues of managing a democratic army and the nature of liberty through the questions and imaginings of teachers. A second historian conducted a walking tour of the collection focusing on three objects, used more as illustrations of his stories rather than inquiry lessons. A university history educator had teachers look at what they learned was a cockroach trap to investigate objects, and also to think about what gets collected in museums, and what anyone knows about 19th century domestic life. A classroom teacher developed a process for having students investigate objects, without the presence of an overall narrative. The continuum along which the historians, history educators, and the lead teachers worked with museum objects could be variously described as one between content and pedagogy, narrative and singular item, object and context, or perhaps novice and expert, but all attempt to find ways to make museum collections accessible to students.